Challenges in linking trait patterns to niche differentiation. Issue 10 (7th June 2016) - D'Andrea, Rafael; Ostling, Annette
Abstract : Among approaches to establish the importance of niche differentiation for species coexistence, the use of functional traits is attractive for its potential to suggest specific coexistence mechanisms. Recent studies have looked for trait patterns reflective of niche differentiation, building on a line of research with a deep but somewhat neglected history. We review the field from its foundation in limiting similarity theory in the 1960s to its resurgence in 2000s, and find the theory of trait patterning still in a stage of development. Elements still to be accounted for include environmental fluctuations, multidimensional niche space, transient dynamics, immigration, intraspecific variation, evolution and spatial scales. Recent empirical methods are better than early approaches, but still focus on patterning arising in simplistic models, and should rigorously link niche space with trait space, use informative null models, and adopt new metrics of pattern as theory develops. Because tests based on overly simplistic expectations of trait pattern are of little value, we argue that progress in the field requires theory development, which should entail exploring patterns across a set of conceptual and system‐specific models of competition along trait axes. Synthesis Traits relate to ecological performance and are easy to measure. Trait patterns can thus be a practical tool for inferring community assembly processes, and have been extensively used for this purpose. Classical trait patterning theory dates back to the 1960s, and despite heavy criticism still persists in empirical studies. Here we highlight steps needed for traits to realize their potential. These include firmly linking them to niche axes, and updating pattern expectations to consider recent results from models of niche dynamics, such as the emergence of species clusters. Further theory development should reveal whether there is a common traits‐based signature across different niche mechanisms.